PENGARUH KETERLIBATAN KERJA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Badan Pendapatan Daerah Kota Semarang) - Rifki Alan Aldiansyah; Tristiana Rijanti (Value : Jurnal Manajemen dan Akuntansi, 2021)
Abstract This study aims to determine the effect of job involvement, motivation, and work environment on employee performance in the Regional_Revenue_Agency of Semarang City. The number of respondents who became the sample in the study were 101 employees_and based on the simple random sampling . The results of the study were analyzed using multiple linear regression with the help of the SPSS 22 program. The results of the analysis show that: (1) Job Involvement has a positive and significant effect on and Employees Employee Performance (2) Motivation has a positive and significant effect on Employee_Performance (3) The Work Environment_has a positive and significant effect on Employees Performance. Keywords : Job Involvement, Motivation, , Work Environment and Employees Performance